1989
DOI: 10.1007/bf00221215
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of subcellular calcium in rat liver on administration of vanadate

Abstract: Mitochondria isolated from the livers of rats administered with sodium meta-, ortho-, or polyvanadate, but not vanadyl sulphate, exhibited enhanced Ca2+ -stimulated respiration and uptake of calcium. These effects were shown also by mitochondria isolated from livers perfused with polyvanadate. The concentration of acid-soluble calcium decreased significantly in the mitochondrial fraction on vanadate treatment, while that in the cytosol showed a corresponding increase. Phenoxybenzamine, an antagonist to alpha-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results of our study are well in congruence with this report. 32 Furthermore, it is also reported that stimulation of lipid peroxidation increases the intracellular content of calcium in isolated rat hepatocytes 33 therefore, it is suggestive that vanadium triggered Ca 2+ - dependent increase in lipid peroxidation. The coadministration (doxycycline + vanadium) to rats exhibited a significant decrease in calcium concentration.…”
Section: Discussionmentioning
confidence: 95%
“…The results of our study are well in congruence with this report. 32 Furthermore, it is also reported that stimulation of lipid peroxidation increases the intracellular content of calcium in isolated rat hepatocytes 33 therefore, it is suggestive that vanadium triggered Ca 2+ - dependent increase in lipid peroxidation. The coadministration (doxycycline + vanadium) to rats exhibited a significant decrease in calcium concentration.…”
Section: Discussionmentioning
confidence: 95%